The Effect of Accounting Information Systems, Internal Control, and Organizational Culture on Employee Performance - Sabrina Alya; Yuliati Yuliati (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
Facing competition in the business world requires companies to have strategies such as superior human resources. The superiority of human resources can be increased through several factors that affect employee performance. This study aims to determine the effect of accounting information systems, internal control, and organizational culture on employee performance at CV. Cahaya Mustika Malang. The type of research used is quantitative research, with the research population consisting of all employees in CV. Cahaya Mustika Malang as many as 35 people. The data analysis used for this research is a data quality test, classical assumption test, Multiple Linear Regression Analysis, and hypothesis testing, tested using SPSS. There are four hypotheses in this study. The results are 1) Accounting Information System has a positive and significant effect on employee performance; 2) Internal Control has a positive and does not have a significant effect on employee performance; 3) Organizational Culture has a positive influence and does not have a significant effect on employee performance; 4) Accounting information systems, internal control, and organizational culture have a simultaneous effect on employee performance.